Children’s right. The senses under tension between the legal framework and the speeches in the mass media - Urdaniz, Anabel (Oficios Terrestres, 2017)
Since 2005, and after a great deal of pressure from popular organizations, in Argentina was created a new legal framework to promote and protect the rights of children and adolescents. Public policies of kirchnerism followed the guidelines of those laws recognising children as holders of rights. After the change of government and the speeches «no poverty» and social equality, which are contrary to the implemented policies, this article seeks to strenghten the concepts around childhood that have been built up to now, carrying out a current analysis on its treatment in the national graphic media..